Implementasi Pendidikan Nilai Surah Al-Ma’un dalam Membentuk Karakter Sosial Peserta Didik di SMP Muhammadiyah 9 Jakarta - Fitri, Anul (Jurnal Pendidikan Islam, 2024)
This research examines the implementation of Surah Al-Ma'un values ​​education in shaping the social character of students. This research focuses on the development of social character faced with challenges, such as globalization and technological advances which have an impact on changes in the way individuals interact. Field study method using observation, interview and documentation data collection techniques to obtain data. By analyzing and comparing various articles related to this subject, this research hopes to describe the form of implementation of QS values ​​education. Al-Maun which has an impact on the formation of the social character of students as the future generation. The results of the research show that the implementation of education in developing social character is very effective when using habituation methods for students, especially at Muhammadiyah 9 Middle School, Jakarta, which has a program that provides regular donations for all school activists. With this habituation, students are able to develop values, attitudes and behavior that can radiate ancestral morals or character. The most important thing is that the key to changing the younger generation for the better is social character education, in order to ensure that students have good character and personality in the future.